Suubi4StrongerFamilies: A study protocol for a clustered randomized clinical trial addressing child behavioral health by strengthening financial stability and parenting among families in Uganda - Ssewamala, Fred M.; McKay, Mary M.; Sensoy Bahar, Ozge; Nabunya, Proscovia; Neilands, Torsten; Kiyingi, Joshua; Namatovu, Phionah; Guo, Shenyang; Nakasujja, Noeline; Mwebembezi, Abel (Frontiers in Psychiatry, 2022)
Background Children in Sub-Saharan Africa are burdened by significant unmet mental health needs. Across the region, high rates of poverty, HIV/AIDS, food insecurity, stigma, and an inadequate health safety net system exacerbate serious child behavioral health needs and impede an effective response. Disruptive behavioral disorders are particularly concerning as they persist through adolescence and adulthood. Hence, addressing the context-specific social influences on child behavioral health is critical given that children in the region comprise more than half of the total regional population. Against this backdrop, this study protocol describes a randomized clinical trial that will examine the mechanisms by which economic empowerment and family strengthening interventions targeting social, familial, and context-specific drivers affect the mental health of children in Uganda. Methods The study uses an experimental, longitudinal design across 30 cluster-randomized primary schools to compare single and combination intervention options; influences of economic empowerment and family strengthening on economic, perceptual, and functioning mediators; and context-specific moderators. The study will be conducted with 900 Ugandan children in mid-upper primary school (10–14 years). The three study conditions (n = 300 each) are: (1) economic empowerment only (EE only), (2) multiple family group-based family strengthening only (MFG-based FS only), and (3) combined EE + MFG-based FS. The interventions will be provided for 12 months; and assessments will occur at baseline, 12, 24, and 36 months. Conclusion Children in Sub-Saharan Africa are burdened by significant unmet mental health needs, including disruptive behavior disorders that persist through adolescence and adulthood if left untreated. The proposed study will examine the mechanisms by which economic empowerment and family strengthening interventions targeting social, familial and context-specific drivers affect the mental health of children in mid-upper primary schools in Uganda. Findings from this study can inform group, community, and population approaches that are needed for scalable solutions to address the social drivers negatively impacting child behavioral health in low-resource settings, including in Sub-Saharan Africa. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT053 68714].